PERAN ORANG TUA DALAM MEMBENTUK KECERDASAN SPRITUAL ANAK DI KELURAHAN SARI REJO KECAMATAN MEDAN POLONIA - Musdalifah, Lis (Fakultas Agama Islam, 2023)
This research aims to: 1) To find out parents in shaping children's spiritual intelligence in Sari Rejo Village 2) To find out children's spiritual intelligence in Sari Rejo Village 3) to find out the role of parents in shaping children's spiritual intelligence in Sari Rejo Village. The type of research used in this research is descriptive qualitative, the location and research object used is in Sari Rejo Village, the researcher uses the research focus, namely the role of parents in forming spiritual intelligence, the withdrawal technique uses random sampling, the research instrument used is an observation guide. , interview guide, documentation notes, data collection techniques used, namely literature including direct quotations and indirect quotations and fieldwork including observation, interviews, data analysis techniques using qualitative descriptive methods. The research results show that the role of parents in shaping children's spiritual intelligence in Sari Rejo Village is very important. One of the efforts or solutions applied by parents is to pay attention to their children from the perspective of Allah SWT's muraqabah, namely by making children feel that Allah SWT always hears their whispers and conversations, sees their every move and knows what is kept secret and hidden so that children will always be used to it. with positive things. Parents must also pay attention to all aspects of children's development, whether in terms of attention, affection, mental education, or matters of faith or belief, and parents must be good role models and act gently towards children because gentle behavior is very helpful in instilling intelligence. spirituality in children.